Le Modèle de Leadership Pour Une Conduite Efficiente de Changement dans les Organisations Internationales en Afrique Subsaharienne Francophone - Dounia Bere M.; Kouadio Patrick Adon (European Scientific Journal, ESJ, 2019)
The overall objective of this multidisciplinary research is to assess the impact of the cultural traits of the French-speaking sub-Saharan Africa on "leadership" in general, and in particular when exercised in a context of organizational change. The research was done on downsizing processes in OCHA Côte d'Ivoire (2013-2014) and ICRISAT Niger (2015), from a multiparadigmatic epistemological perspective (constructivism and empiricism). A qualitative analysis of the primary and secondary data collected on the two processes has yielded results that have confirmed the human dominated cultural theory of leadership attributed by the GLOBE study to the considered area. The characteristics of the leadership styles identified as instrumental in the success of these processes has inspired the main theoretical contribution of the research which is the EMPATHIC and SMART Leadership Model.L’objectif général de cette recherche multidisciplinaire est l’évaluation de l’impact des traits culturels de l’Afrique subsaharienne francophone sur le « leadership » en général, et en particulier, lorsqu’il est exercé dans un contexte de changement organisationnel. La recherche a été faite sur des processus de réduction d’effectifs à OCHA Côte d’Ivoire (2013-2014) et à ICRISAT Niger (2015), à partir d'une perspective épistémologique multiparadigmatique (constructivisme et empirisme). Une analyse qualitative des données primaires et secondaires recueillies sur les deux processus a abouti à des résultats qui ont confirmé la théorie culturelle du leadership à dominante humaine attribuée par l’étude GLOBE à la zone considérée. Les caractéristiques identifiées des styles de leadership qui ont été instrumentaux au succès de ces processus ont inspiré la principale contribution théorique de cette recherche : le modèle de leadership SMART, empreint d’EMPATHIE.